Predicting Sequence Features, Function, and Structure of Proteins Using MESSA. Issue 1 (15th July 2019) - Bhat, Archana S.; Grishin, Nick V.
Abstract: MEta‐Server for protein Sequence Analysis (MESSA) is a tool that facilitates widespread protein sequence analysis by gathering structural (local sequence properties and three‐dimensional structure) and functional (annotations from SWISS‐PROT, Gene Ontology terms, and enzyme classification) predictions for a query protein of interest. MESSA uses multiple well‐established tools to offer consensus‐based predictions on important aspects of protein sequence analysis. Being freely available for noncommercial users and with a user‐friendly interface, MESSA serves as an umbrella platform that overcomes the absence of a comprehensive tool for predictive protein analysis. This article reveals how to access MESSA via the Web and shows how to input a protein sequence to analyze using the MESSA web server. It also includes a detailed explanation of the output from MESSA to aid in better interpretation of results. © 2019 by John Wiley & Sons, Inc.